Phosphoric acid salts of amino acids as a source of oligopeptides on the early Earth - Šponer, Judit E; Coulon, Rémi; Otyepka, Michal; Šponer, Jiří; Siegle, Alexander F; Trapp, Oliver; Ślepokura, Katarzyna; Zdráhal, Zbyněk; Šedo, Ondrej (Communications chemistry, 2024)
Because of their unique proton-conductivity, chains of phosphoric acid molecules are excellent proton-transfer catalysts. Here we demonstrate that this property could have been exploited for the prebiotic synthesis of the first oligopeptide sequences on our planet. Our results suggest that drying highly diluted solutions containing amino acids (like glycine, histidine and arginine) and phosphates in comparable concentrations at elevated temperatures (ca. 80 °C) in an acidic environment could lead to the accumulation of amino acid:phosphoric acid crystalline salts. Subsequent heating of these materials at 100 °C for 1-3 days results in the formation of oligoglycines consisting of up to 24 monomeric units, while arginine and histidine form shorter oligomers (up to trimers) only. Overall, our results suggest that combining the catalytic effect of phosphate chains with the crystalline order present in amino acid:phosphoric acid salts represents a viable solution that could be utilized to generate the first oligopeptide sequences in a mild acidic hydrothermal field scenario. Further, we propose that crystallization could help overcoming cyclic oligomer formation that is a generally known bottleneck of prebiotic polymerization processes preventing further chain growth.